Professores/as negros/as: trajetórias e tentativas de cooptação docente - Bueno, Rogério Donizetti (2021)
This research has as its general objective to analyze, from the perspective of historical material-ism, the possibilities and modes of co-optation of black teachers in the neoliberal capitalist system. The specific objectives are: a) to historically reconstruct the insertion of the negro in the capitalist system and its double process of alienation; b) to understand the mechanisms of insertion or exclusion of black teachers in the trajectory of schooling, academic-university and work. Methodologically, this is a research of a qualitative approach, of bibliographic-documentary type, descriptive, argumentative, and analytical approach regarding the objec-tives. Data construction techniques are: survey of documents produced by INEP and IBGE, review of theses and dissertations on the website of the Digital Library of Theses and Disser-tations (BDTD) and articles in academic journals (SciELO), and interview with semi-structured script, recorded in audio, followed by transcription, systematization and analysis of the following categories: Alienation; Reification; Cooptation. The sampling of deponent sub-jects consists of five black teachers of higher education, from various institutions of private and public origin. The theoretical framework used focuses on the historical materialistic per-spective, using authors such as Florestan Fernandes, Caio Prado Junior, Clóvis Moura, José Carlos Mariátegui, Antônio Gramsci and others who take Karl Marx's work as an analytical basis and the concepts of alienation, reification, co-optation. We indicate the existence of structural racism, related to the economic system and corresponding institutional, social and cultural conditions, in which there are a series of contradictions and gradations between the condition of co-optation and autonomy.